Media, Fear of Crime, and Authority: Focus Groups in Lima (Perú) - Dammert-Guardia, L (Springer Science and Business Media Deutschland GmbH, 2022)
Lima’s news agenda focuses on the media’s exposure and coverage of crime. This paper aims to analyze the relationship between news consumption, fear of crime, and trust in authority. To this end, twelve focus group discussions were conducted with residents of Lima. The findings revealed significant vicarious fear: respondents admitted to feeling greater fear for their children and other relatives as they remembered recent news reports. Additionally, the focus groups related news consumption to a paucity of trust in authority and evidenced a subjective consonance with their environment. © 2022, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.